Presence of pathogenic Leptospira spp. in the reproductive system and fetuses of wild boars (Sus scrofa) in Italy. - Giovanni Cilia; Fabrizio Bertelloni; Ivana Piredda; Maria Nicoletta Ponti; Barbara Turchi; Carlo Cantile; Francesca Parisi; Paolo Pinzauti; Andrea Armani; Bruna Palmas; Malgorzata Noworol; Domenico Cerri; et al. (Public Library of Science (PLoS), 2020)
Leptospirosis is a re-emerging and globally spread zoonosis caused by pathogenic genomospecies of Leptospira. Wild boar (Sus scrofa) are an important Leptospira host and are increasing in population all over Europe. The aim of this investigation was to evaluate Leptospira spp. infection in the reproductive systems of wild boar hunted in two Italian regions: Tuscany and Sardinia. From 231 animals, reproductive system tissue samples (testicles, epididymides, uteri) as well as placentas and fetuses were collected. Bacteriological examination and Real-Time PCR were performed to detect pathogenic Leptospira (lipL32 gene). Leptospires were isolated from the testicles and epididymides of one adult and two subadult wild boar. Four isolates from the two subadult males were identified as Leptospira interrogans serogroup Australis by MLST, whereas Leptospira kirschneri serogroup Grippotyphosa was identified from the adult testicles and epididymis. Using Real-Time PCR, 70 samples were positive: 22 testicles (23.16%) and 22 epididymides (23.16%), 10 uteri (7.35%), 3 placentas (6.66%), and 13 fetuses (28.88%). Amplification of the rrs2 gene identified L. interrogans and L. kirschneri species. The results from this investigation confirmed that wild boar represent a potential source of pathogenic Leptospira spp. Isolation of Leptospira serogroups Australis and Grippotyphosa from the male reproductive system and the positive Real-Time PCR results from both male and female samples could suggest venereal transmission, as already demonstrated in pigs. Furthermore, placentas and fetuses were positive for the lipL32 target, and this finding may be related to a possible vertical transmission of pathogenic Leptospira.